Konseling Keluarga untuk Mewujudkan Keharmonisan Rumah Tangga dalam Al-Qur’an dan Hadits - Atfi Kusminar (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2025)
Family life is a journey formed by two people who are bound by marriage. In the course of life there will always be problems that come your way, whether they originate from within or from outside the individual who is living it. In creating a harmonious household, problematic phenomena are often found in the family such as quarrels, jealousy, infidelity, differences in income, differences in life principles and which lead to divorce. This research is a literature review approach sourced from books about creating household harmony using family counseling. Various family problems can be resolved through family counseling. Family counseling can help family members achieve harmony in the family because in the counseling process, the counselee will try to know, recognize, pay attention to, accept and try to maintain their family. Family counseling can help prevent and overcome problems in the family so that the counselee can maintain family harmony.